Development curve of the best results of female para swimmers in the 200 individual medley in the SM8 class - Perzel, I.; Zoretic, D.; Milanovic, D. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The aim of this study is to analyse the trend and determine the development curve of the eight and three best results and the best result in the world among female para-swimmers in the SM8 class in the 200 m individual medley. According to the statistically determined results, there is no statistical significance in any of the data sets. We can conclude that the results of the world's best female para-swimmers in the 200 m individual medley of the SM8 class show a small tendency for their constant progress which are significantly influenced by events at the global level and changes in the rules for para-swimming.